DIACHRONIC AND SYNCHRONOUS MANIFESTATIONS OF POLISH INFLUENCES IN THE FEMINITIVE SUBSYSTEM OF THE UKRAINIAN LANGUAGE - Brus, Maria (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Goal. The article examines the Ukrainian-Polish language ties and analyzes the feminine forms of Polish origin that entered the Ukrainian lexicon in different historical periods, its active or passive composition and left an impression on the feminine subsystem of the Ukrainian language. It is noted that the first feminitives-polonisms appeared in the Old Ukrainian language in the 14th - 15th centuries, increased in number in the 16th - 17th centuries, and then replenished the Ukrainian vocabulary to a small extent, and mainly with words motivated by masculinatives of Polish origin.Research methodology. In the context of the establishment and formation of interlanguage interaction, the problem of creation and use of feminitives is today one of the actualized and ambiguously interpreted, the disclosure of which activates international cooperation and communication to a certain extent. At the Polish-Ukrainian level, this problem is not modern, but has a long history, so its research is based on the use of diachronic and synchronous approaches. From the point of view of the influence of the Polish language on the feminine subsystem of the Ukrainian language, the diachronic aspect made it possible to trace the chronology of borrowing from the Polish language of feminines or their creative bases throughout the entire written age,and synchronous - to analyze the peculiarities of borrowed nominations from the Polish language at different historical stages. To implement these approaches, historical, descriptive, and partly comparative methods, elements of lexical, word-forming, and stylistic analysis were used. Scientific works on linguistic Ukrainian studies on Polish-Ukrainian language connections and feminine borrowings from the Polish language are taken as the theoretical base, and historical and explanatory dictionaries of the Ukrainian language are the main source base.